The Exact Solutions of the Conformable Time-Fractional Modified Nonlinear Schrödinger Equation by the Trial Equation Method and Modified Trial Equation Method - Safoura Rezaei Aderyani; Reza Saadati; Javad Vahidi; Tofigh Allahviranloo (Advances in Mathematical Physics)
Using the trial equation method (TEM) and modified trial equation method (MTEM), firstly, we find the analytical solutions of the conformable time-fractional modified nonlinear Schrödinger equation (CTFMNLSE), and finally, we present numerical results in tables and charts.